PENGGUNAAN PERMAINAN KARTU UNTUK PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SEKOLAH DASAR - Hariato, Rudi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The aim of this research was to describe how to use card game in improving the student beginning reding ability. This research was action research using qualitative and quantitative approaches. Subjects in thisresearch were teacher and the first grade students at SDN Aia Kumayan Agam Regency. The result showed that there was an increase on student beginning reading ability. The averege of student’s learning outcome in the first cycle was 68.86, it increased in the second cycle to 88.88.   Kata kunci: keterampilan membaca permulaan; permainan kartu